2017
DOI: 10.1002/ejhf.921
|View full text |Cite
|
Sign up to set email alerts
|

The autonomic nervous system as a therapeutic target in heart failure: a scientific position statement from the Translational Research Committee of the Heart Failure Association of the European Society of Cardiology

Abstract: Despite improvements in medical therapy and device‐based treatment, heart failure (HF) continues to impose enormous burdens on patients and health care systems worldwide. Alterations in autonomic nervous system (ANS) activity contribute to cardiac disease progression, and the recent development of invasive techniques and electrical stimulation devices has opened new avenues for specific targeting of the sympathetic and parasympathetic branches of the ANS. The Heart Failure Association of the European Society o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
121
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 149 publications
0
121
1
1
Order By: Relevance
“…Imbalanced neuro‐endocrine activation and control of the myocardium and circulation is understood as a cornerstone of HF pathophysiology and a driving force of disease progression and high mortality of HF. Consequently, autonomic nervous system abnormalities have been a recent and exciting therapeutic target in HF . There are multiple cardiopulmonary reflexes that interact to keep blood pressure, heart rate, cardiac output, peripheral blood flow, fluid volume balance, ventilation, V/Q matching, arterial blood gases, and the metabolic state of the metabolizing tissues stable, even in illness, or during environmental or exertional stress ( Figure ) .…”
Section: Brain Stem Function – Neuro‐vegetative Controlmentioning
confidence: 99%
“…Imbalanced neuro‐endocrine activation and control of the myocardium and circulation is understood as a cornerstone of HF pathophysiology and a driving force of disease progression and high mortality of HF. Consequently, autonomic nervous system abnormalities have been a recent and exciting therapeutic target in HF . There are multiple cardiopulmonary reflexes that interact to keep blood pressure, heart rate, cardiac output, peripheral blood flow, fluid volume balance, ventilation, V/Q matching, arterial blood gases, and the metabolic state of the metabolizing tissues stable, even in illness, or during environmental or exertional stress ( Figure ) .…”
Section: Brain Stem Function – Neuro‐vegetative Controlmentioning
confidence: 99%
“…54 A secondary analysis of the data by Ridker et al 55 showed a reduction of lung cancer incidence (with 150 and 300 mg canakinumab vs. placebo) and lung cancer mortality (with 300 mg of canakinumab vs. placebo). These effects might be related to a sympathetic activation in some patients, like it has been shown for HF 60 . Dr Markus Anker (Berlin, Germany) discussed CV problems of cancer patients beyond anti-cancer therapy Cardio-oncology at Heart Failure Congress 2019 associated cardiotoxicity.…”
Section: Cardiovascular Disease In Cancermentioning
confidence: 66%
“…A recent analysis in 305 advanced colorectal adenoma patients suggested higher adenoma recurrence rates in those patients with higher heart rates 59 . These effects might be related to a sympathetic activation in some patients, like it has been shown for HF 60 . More studies are needed to better understand the underlying mechanisms.…”
Section: Cardiovascular Disease In Cancermentioning
confidence: 66%
“…Other topical issues covered including cancer in HF by the cardio‐oncology sub‐committee, and a proposed taxonomy of heart and brain interactions complicating HF by the Heart and Brain Sub‐Committee as well as a practical guidance paper from the Study Group on Peripartum Cardiomyopathy . There were also important papers from our translational scientist colleagues, including one from the Translational Research Committee on the autonomic nervous system as a therapeutic target in HF, and two from the affiliated Working Group on Myocardial Function, one covering an integrative translational approach to study HFpEF and a second on the innate immune system in chronic cardiomyopathy . The HFA has never looked stronger.…”
mentioning
confidence: 99%